2020
DOI: 10.1101/2020.08.10.20171652
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid Detection of SARS-CoV-2 Antibodies Using Electrochemical Impedance-Based Detector

Abstract: Emerging novel human contagious viruses and pathogens put humans at risk of hospitalization and possibly death due to the unavailability of vaccines and drugs which may take years to develop. Coronavirus disease (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was classified as a pandemic by theWorld Health Organization and has caused over 550,000 deaths worldwide as of July 2020. Accurate and scalable point-of-care devices would increase screening, diagnosis, and monitoringof … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…15 The electrochemical biosensor detection method is rapid, low cost, easy operation, small sample size, and portable, allowing on-the-spot testing, as well as high sensitivity and selectivity for medical sample analysis. 13,15–20…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 The electrochemical biosensor detection method is rapid, low cost, easy operation, small sample size, and portable, allowing on-the-spot testing, as well as high sensitivity and selectivity for medical sample analysis. 13,15–20…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Several studies have also reported the use of electrochemical biosensors to detect the SARS-CoV-2 virus. Some of them are: the electrochemical immunosensor by using a working electrode functionalized with graphene-anti-spike for detection of the RBD, 11 modication of electrode using cobalt-TiO nanotubes (Co-TNTs) monoclonal antibody as a detection platform for SARS-CoV-2, 1 modied carbon black printed electrode with magnetic beads and antibodies, 12 PET-gold electrode with monoclonal antibody, 13 functionalized gold nanoparticle (AuNP)/nCoV-19Ab), 9 e-Covsens based on SPCE-Ab nCovid-19 with uorine-doped tin oxide electrode (FTO-AuNPs), 14 and a ProtA/CuONC nano-bio device-SPCE as a substrate to direct the orientation of IgG antibodies, as a specic receptor for the detection of spike glycoproteins. 15 The electrochemical biosensor detection method is rapid, low cost, easy operation, small sample size, and portable, allowing on-the-spot testing, as well as high sensitivity and selectivity for medical sample analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, antibodies, such as IgM and IgG, from patient samples can also be detected to probe the infection history [8]. Diverse techniques have been developed to analyze SARS-CoV2, such as real-time polymerase chain reaction (PCR) [9], colorimetric assay [10], surface plasmon resonance (SPR) and localized SPR [11], electrochemical approaches [9,[12][13][14][15], optics methods [16,17], optical/ chemiluminescence immunosensors [18], fluorescent technique [19], wearable sensor [20], and isothermal rolling circle amplification (RCA) [21]. Although many studies have focused on the sensitive determination methods of SARS-CoV-2 [22][23][24][25], COVID-19 has resulted in a heavy burden for health systems and human society.…”
Section: Introductionmentioning
confidence: 99%